Long-Term Outcomes of Breast Cancer Patients Receiving Levobupivacaine Wound Infiltration or Diclofenac for Postoperative Pain Relief - Josipa Glavas Tahtler; Dajana Djapic; Marina Neferanovic; Jelena Miletic; Marta Milosevic; Kristina Kralik; Nenad Neskovic; Ilijan Tomas; Dora Mesaric; Ksenija Marjanovic; Jasmina Rajc; Zelimir Orkic; et al. (MDPI AG, 2023)
Breast cancer is the most common malignant disease in women. Preclinical studies have confirmed that the local anesthetic levobupivacaine has a cytotoxic effect on breast cancer cells. We examined whether postoperative wound infiltration with levobupivacaine influences survival in 120 patients who were operated on for breast cancer and underwent quadrantectomy or mastectomy with axillary lymph node dissection. Groups with continuous levobupivacaine wound infiltration, bolus wound infiltration, and diclofenac analgesia were compared. Long-term outcomes examined were quality of life, shoulder disability, and hand grip strength (HGS) after one year and survival after 5 and 10 years. Groups that had infiltration analgesia had better shoulder function compared to diclofenac after one year. The levobupivacaine PCA group had the best-preserved HGS after 1 year (P = 0.022). The most significant predictor of the 5-year outcome was HGS (P = 0.03). Survival at 10 years was 85%, 92%, and 77% in the diclofenac, levobupivacaine bolus, and levobupivacaine PCA groups (ns. P = 0.36). The extent of the disease at the time of surgery is the most important predictor of long-term survival (P = 0.03). A larger prospective clinical study could better confirm the effect of levobupivacaine wound infiltration on outcomes after breast cancer surgery observed in this pilot study-trial number NCT05829707.